2007
DOI: 10.1007/s00125-007-0842-6
|View full text |Cite
|
Sign up to set email alerts
|

Glucose fluctuations and activation of oxidative stress in patients with type 1 diabetes

Abstract: Aims/hypothesis Glucose fluctuations may help predict diabetic complications. We evaluated the relation between glucose variability and oxidative stress in patients with type 1 diabetes. Methods Continuous glucose monitors were inserted subcutaneously in 25 patients. During the measurement, patients collected two 24 h urine samples, while 24 healthy controls collected one 24 h urine sample for determination of 15(S)-8-iso-prostaglandin F 2a PGF 2a ð Þ using HPLC tandem mass spectrometry. Mean of the daily diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
125
6
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(142 citation statements)
references
References 35 publications
5
125
6
6
Order By: Relevance
“…On the other hand, a number of studies have found no such associations (16,24,25). The lack of correlation between inflammatory bioma rkers and levels of fasting glucose or HbA1c may sug gest that, once triggered, inflammatory response can be modulated positively or negatively by parameters other than those studied, including, for example, glucose excursions (12). This hypothesis simply reinforces the complexity and multifactorial nature of T1DM.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, a number of studies have found no such associations (16,24,25). The lack of correlation between inflammatory bioma rkers and levels of fasting glucose or HbA1c may sug gest that, once triggered, inflammatory response can be modulated positively or negatively by parameters other than those studied, including, for example, glucose excursions (12). This hypothesis simply reinforces the complexity and multifactorial nature of T1DM.…”
Section: Discussionmentioning
confidence: 94%
“…Several authors have stated that, in patients with T1DM, no significant pathological consequences of diabetes can be detected earlier than 5 years from onset (10), even though sig nificant increases in ROS generation can be detected in patients at the onset of the disease (11). These findings suggest that the structural and functional changes in volved in diabetic complications may commence at the onset of the hyperglycemic trigger, and it is possible that, in the presence of persistent acute peaks or chro nic hyperglycemia, inflammatory metabolic and immu nological pathways can become activated at all times after diagnosis (12).…”
Section: Introductionmentioning
confidence: 99%
“…Measures of glycemic variability were also calculated (22), including the following: SD of mean CGM glucose levels, which shows how much variation there is from the average; M-value (23), which is a measure of variability, calculated using a formula from each glucose value, and then divided by the total number of glucose values to produce a mean; mean amplitude of (positive + and negative 2) glycemic excursions (MAGE+/2), which summarizes glycemic variability by identifying glucose peaks and troughs whose amplitudes lie .1 SD outside of the mean (24); lability index (LI), which is a score based on the change in glucose levels over time (25); J-index, which is calculated using mean glucose levels and their SD (26); average daily risk ratio (ADRR), which is calculated by transforming each glucose value and then attributing risk to the transformed point so that it is possible to generate the risk attributed to low glucose (RLBG) and high glucose (RHBG) (27); glycemic risk assessment in diabetes equation (GRADE), which summarizes the degree of risk associated with variability in glucose profile (a score of ,5 indicates well-controlled glucose profiles in the nondiabetic range and a score of .5 indicates periods of clinically significant hypo or hyperglycemia [28]); and mean absolute glucose (MAG), which calculates the sum of differences between successive glucose values divided by the total time over which these values are recorded (29).…”
Section: Summary Statistical Analysismentioning
confidence: 99%
“…The most favored assumption so far by means of which hyperglycemic induced complication can occur is by means of reactive oxygen species [6]. Many ocular diseases are related to damage caused by oxidative stress [7]. Recent data in the literature by Kao et al [8], support an important role of oxidative damage in promoting cataract formation.…”
Section: Discussionmentioning
confidence: 99%